Perfil dos pacientes com fibrose cística atendidos no centro de referência pediátrico do Espírito Santo (Brazilian Journal of Health Research, 2019)
Profile of patients with cystic fibrosis assisted at the Pediatric Referral Center of Espírito Santo State